The longest ride - Sparks, Nicholas (New York Grand Central Publishing, 2013)
The lives of 91-year-old Ira Levinson, young cowboy Luke, and Wake Forest College senior Sophia Danko converge in an extraordinary and unexpected way as Ira clings to his wife Ruth's words and his memories and Sophia finds herself imagining a future far removed from her plans.
Keywords: Unmarried couples -- Fiction; Man-woman relationships -- Fiction; Life change events -- Fiction; Large type books